PENGARUH LITERASI KEUANGAN SYARIAH DAN KEPERCAYAAN NASABAH TERHADAP KEPUTUSAN MENABUNG HAJI JANGKA PANJANG DI BANK SUMUT SYARIAH - Tengku Imam Alwafi; Muhammad Irwan Padli Nasution; Andri Soemitra (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the influence of Islamic financial literacy and customer trust on the decision to engage in long-term Hajj savings among customers of Bank Sumut Syariah. Using a quantitative, causal-associative approach, the research surveyed 100 active Hajj savings customers in Medan City, selected through the Slovin formula, via a five-point Likert-scale questionnaire. Data were analyzed using multiple linear regression in IBM SPSS Statistics version 25. The results show that Islamic financial literacy partially has a positive and significant effect on the Hajj savings decision (t = 2.881, sig. = 0.005 < 0.05). Customer trust likewise has a positive and significant effect (t = 3.555, sig. = 0.001 < 0.05). Simultaneously, both variables significantly influence the Hajj savings decision (F = 52.347, sig. = 0.000 < 0.05), with an R² of 0.519, indicating that Islamic financial literacy and customer trust jointly explain 51.9% of the variance in the decision, while the remaining 48.1% is attributable to factors outside the scope of this study. These findings suggest that enhancing Islamic financial literacy and strengthening customer trust are key drivers of long-term Hajj savings decisions. Accordingly, Bank Sumut Syariah is encouraged to improve its sharia financial literacy education programs and reinforce trust-building strategies to boost public interest and commitment to long-term Hajj savings.